Решите уравнение: 2sin^2 (x) + 3sin (x) * cos (x) - 2cos^2 (x) = O

+3
Ответы (1)
  1. 30 августа, 16:22
    0
    1. Разделим обе части уравнения на cos^2 (x):

    2sin^2 (x) + 3sinx * cosx - 2cos^2 (x) = 0;

    2sin^2 (x) / cos^2 (x) + 3sinx * cosx / cos^2 (x) - 2cos^2 (x) / cos^2 (x) = 0;

    2tg^2 (x) + 3tgx - 2 = 0.

    2. Решим квадратное уравнение относительно tgx:

    D = b^2 - 4ac;

    D = 3^2 - 4 * 2 * (-2);

    D = 9 + 16 = 25;

    tgx = (-b ± √D) / (2a);

    tgx = (-3 ± √25) / (2 * 2);

    tgx = (-3 ± 5) / 4.

    1) tgx = (-3 - 5) / 4 = - 8 / 4 = - 2;

    x = - arctg2 + πk, k ∈ Z.

    2) tgx = (-3 + 5) / 4 = 2 / 4 = 1/2;

    x = arctg (1/2) + πk, k ∈ Z.

    Ответ: - arctg2 + πk; arctg (1/2) + πk, k ∈ Z.
Знаешь ответ на этот вопрос?